Influence of Groundcover Vegetation, Soil Physicochemical Properties, and Irrigation Practices on Soil Fungi in Semi-arid Vineyards - Vukicevich, Eric; Lowery, D. Thomas; Bennett, Jonathan A.; Hart, Miranda (Frontiers in Ecology and Evolution, 2019)
Although plants are known to have a strong influence on soil biota, the effect of groundcover vegetation in perennial cropping systems on soil fungi has been little explored. We surveyed extensively managed vineyards to determine how plant community functional characteristics, soil factors, and irrigation management related to the abundance of two guilds of soil fungi that may play a role in plant-soil feedback (entomopathogenic fungi represented by Beauveria bassiana, and the pathogenic species complex, Ilyonectria spp.). We found that plant community characteristics were related to fungal abundance for both fungi assayed. Beauveria bassiana increased with native species, annual plants, and legumes consistently across sampling periods. Ilyonectria spp. increased with the abundance of forbs and exotic species, though only the relationship with forbs was consistent across sampling periods. Both fungal guilds increased with increasing soil organic matter. The use of dual or sprinkler irrigation systems also increased Beauveria bassiana and Ilyonectria spp. in vineyard soils. Overall, groundcover vegetation played a significant role in driving abundance of these important groups of soil fungi. Groundcover management may therefore be a viable tool to manipulate soil fungi with the potential for improving ecosystem services such as conservation biological control of soil dwelling insect pests and deterring pathogens in perennial cropping systems.